Learning nature in schools: Benjamin contra Dietzgen on nature's 'free gifts'. Issue 3 (April 2019) - Boxley, Simon
When we learn nature, do we encounter her as 'free' in the sense of having neither cost nor price? Is she something 'given'? And is that which nature offers us 'gratis'? In the UK, many schoolchildren have been encouraged to 'give thanks' for nature's gifts. But why, if she is free, give thanks; and thanks to whom? If one learns to encounter nature as 'free', is she then really free for the taking? Walter Benjamin notably derided Joseph Dietzgen for regarding what nature supplies to humanity as 'gratis', and long argument has continued among Marxists since Benjamin's time concerning how we regard nature's 'gifts'. This paper addresses the ideological appropriation of nature, and makes this a pedagogical question best approached through readings of Benjamin and Dietzgen. It does so in a context where education policy reflects little if any concern with the acquisition of a disposition towards nature among children.